The study of extended single minute exchange of die (SMED) method in 1200 tonnage tandem press line for operation improvement - Azizul Qayyum, Basri; N. M. Zuki, N. M. (Universidade NOVA de Lisboa, Portugal, 2017)
Single-Minute Exchange of Die (SMED) is a popular method used to optimize the die change processing time. The purpose of this study is to identify on how to reduce setup time by using Extended SMED in automotive stamping line. An actual case study at an automotive company in Malaysia was conducted based on parts supply failure cases. The observations, assessments and standard manufacturing implementation were carried out during the study. WITNESS simulation software was used in this study to identify the critical processes and also enable the validation of actual output based on the production planning. The result of the particular 1200 tonnage press line which produced six parts in one shift of operation with small lot size design has been identified and improved. The outstanding improvement based on the Extended SMED compares to conventional SMED approach shows a decreasing changeover time from an average of 20.13 minute to 9.35 minute which is 53 % reduction.